Analysis of the Effect of Economic Growth on Regional Inequality in Aceh Province in 2017 - Dela, Ani; Amanda, Amanda; Desmawan, Deris (Journal Of Accounting Management Business And International Research, 2022)
Making this journal aims to fulfill one of the tasks of the development economics course with lecturer Deris Desmawan, SE, M.Si. This study aims to examine the relationship between the effect of economic growth on regional inequality for the period 2017. This study uses secondary data, namely data sourced from BPS as well as previous studies that discuss the same topic. There are variable, namely economic growth and regional inequality. The results show the variable of economic growth on regional inequality has no significant full effect on regional inequality.